2023
DOI: 10.3389/fpsyg.2023.1079196
|View full text |Cite
|
Sign up to set email alerts
|

How self-leadership promotes job crafting: Based on the perspective of self-determination theory

Abstract: According to self-determination theory, the present study develops a moderated mediation model to investigate how and when self-leadership promotes employees’ job crafting, emphasizing the mediating effect of autonomous motivation and the moderating effect of leader empowering behavior. We analyze and test the hypotheses based on 269 valid three-wave data from employees. The findings show that self-leadership has a significantly positive impact on job crafting, and a positive indirect effect on job crafting vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The ability to self-lead can influence individuals to utilize the various specific behavioral and cognitive techniques to regulate their conduct, thereby enhancing their effectiveness and proactive engagement within the professional realm [32]. Study [33] shows that students possessing elevated levels of self-leadership abilities demonstrate more refined selfmonitoring behaviors, directing their endeavors towards career advancement.…”
Section: Self-leadership On Career Aspirationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to self-lead can influence individuals to utilize the various specific behavioral and cognitive techniques to regulate their conduct, thereby enhancing their effectiveness and proactive engagement within the professional realm [32]. Study [33] shows that students possessing elevated levels of self-leadership abilities demonstrate more refined selfmonitoring behaviors, directing their endeavors towards career advancement.…”
Section: Self-leadership On Career Aspirationsmentioning
confidence: 99%
“…Research [3] shows that statistical calculations indicate that short-term study abroad not only significantly affects leadership skills but also the career aspirations of students. Liu et al [39] reveals that self-leading employees have autonomy and control over their tasks, making them want to change and reshape their work, leading to better career outcomes. Additionally, self-leadership refers to behaviors and thoughts that influence oneself to enhance work interests, which are vital tools for students and future organizational success [40].…”
Section: Self-leadership Moderates the Effect Of Student Exchange Pro...mentioning
confidence: 99%
“…Self-goal setting is a behavior-centered strategy that can promote individual creativity (Zeijen et al, 2018), which is beneficial for creatively Self-goal setting and career sustainability constructing an individual career. Individuals who adopt self-goal setting undertake proactive behavior toward their desired goals (Liu et al, 2023;Parker and Liao, 2016). Researchers have found that setting goals can enhance self-regulation (Latham and Locke, 1991), which involves striving to guide one's thoughts, feelings and actions to achieve one's goals (Zimmerman, 2000).…”
Section: Model Development and Hypothesesmentioning
confidence: 99%
“…What's more, employees can enhance their self-awareness through behavior-centered self-goal setting strategies, as well as enhancing their self-directed efforts when performing important but potentially unpleasant tasks (Neck and Houghton, 2006). This self-awareness also enables them to reflect on their career development by continually considering and judging whether their actual behaviors are consistent with their goals (Liu et al ., 2023). The process of continuously evaluating goals constitutes positive career reflection, which is one of the dimensions of career crafting (Tims and Akkermans, 2020).…”
Section: Model Development and Hypothesesmentioning
confidence: 99%